math/algebra

posted by .

can someone check my work?
x^2 = 22
xãx-22

if x^2 is 22, then x is +- sqrt 22

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] …
  2. math,algebra,help

    Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
  3. algebra

    Can someone please help me with this one?
  4. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  5. Algebra 1

    sqrt r - sqrt s/ sqrt r + sqrt s =r sqrt r- sqrt rs +sqrt s/ r can someone check this for me please.
  6. Algebra

    Can someone please tell me if my work and solution looks correct. I am a little unsure of whether or not I did it correctly. Equation: sqrt(x+2) - x = 0 sqrt(x+2) = x x + 2 = x^2 x^2 - x - 2 = 0 (x-2)(x+1) = 0 x = 2 and x = -1 -1 does …
  7. Cody

    Write the following with rational, positive exponents. a. sqrt of 8 = 8^1/2 b. seventh root of 5^2 = 5^2/7 c. sqrt sqrt 6 = ?
  8. Algebra-drwls please check!

    Posted by Megan on Tuesday, October 12, 2010 at 3:44pm. I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) …
  9. Algebra

    Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?
  10. Math

    Find of g(f(x)) when f(x)=sqrt(x+3) and g(x)=(x^2+2)/x. a. g(f(x))=(x^2+2)(sqrt(x+3))/x b. g(f(x))=(x+5)/(sqrt(x+3)) c. g(f(x))=(x^2+6x+11)/(sqrt(x+3)) d. g(f(x))=(sqrt(((x^2+2)/x)+3) Every time I work this problem, I get some crazy …

More Similar Questions